Fully fuzzy fixed charge multi-item solid transportation problem - Giri, Pravash Kumar; Maiti, Manas Kumar; Maiti, Manoranjan (Applied soft computing, 2015)
[Display omitted] •Fully fuzzy fixed charge multi-item solid transportation problem (FFFCMISTP) is considered.•FFFCMISTP with the decision variable are taken as fuzzy.•New defuzzification method, fuzzy slack and surplus variable is used for FFFCMISTP.•Minimization of transportation cost as well as fuzziness of the solution for FFFCMISTP is discussed. This paper presents fully fuzzy fixed charge multi-item solid transportation problems (FFFCMISTPs), in which direct costs, fixed charges, supplies, demands, conveyance capacities and transported quantities (decision variables) are fuzzy in nature. Objective is to minimize the total fuzzy cost under fuzzy decision variables. In this paper, some approaches are proposed to find the fully fuzzy transported amounts for a fuzzy solid transportation problem (FSTP). Proposed approaches are applicable for both balanced and unbalanced FFFCMISTPs. Another fuzzy fixed charge multi-item solid transportation problem (FFCMISTP) in which transported amounts (decision variables) are not fuzzy is also presented and solved by some other techniques. The models are illustrated with numerical examples and nature of the solutions is discussed.